Microbubble-enriched lavage fluid for treatment of experimental peritonitis. - Sharma, P; Rakhorst, G; Engels, E; van der Mei, H; Busscher, H; Ploeg, R (2008)
BACKGROUND: Relaparotomies and closed postoperative peritoneal lavage (CPPL) are performed to treat persistent peritonitis. This experimental animal study compared open abdominal lavage with CPPL, and evaluated the potential of microbubble-enriched lavage fluids to improve the efficiency of CPPL and reduce clinical morbidity, mortality and cost. METHODS: Fluorescent polystyrene spheres were injected intraperitoneally into 22 male Wistar rats to simulate localized peritonitis. After 18 h the rats received open abdominal lavage and CPPL, with and without microbubbles. Microbubbles were obtained by adding ultrasound contrast agents to continuous ambulatory peritoneal dialysis fluid. RESULTS: Open abdominal lavage was 3.5 times more effective in particle removal than CPPL, owing to better fluid dynamics. The introduction of air-liquid interfaces in the form of microbubbles made CPPL up to 2.4 times more effective than lavage without bubbles. Best detachment results were obtained when microbubbles with a flexible surfactant shell and longer blood elimination half-life were used. CONCLUSION: Open abdominal and CPPL lavage techniques are not efficient beyond a certain duration and volume as they do not cause bacterial detachment from the peritoneal membrane. Using surface tension forces from microbubbles significantly enhanced polystyrene particle detachment. These findings may have great consequences for the treatment of patients with peritonitis.